The impact beyond cancer of the HPV vaccine - Carvalho, Newton Sergio de; Moron, Gabriela de Almeida Pernambuco; Bertelli, Júlia (Brazilian Journal of Sexually Transmitted Diseases, 2020)
The incidence of 16,370 new cases of cervical cancer was recorded in Brazil during the year of 2018 with 5,000 deaths1. Regarding the low coverage of HPV vaccination in Brazil, we decided to write this letter to show that maybe there are some benefits of this vaccine beyond the oncogenesis process. This news could be increasing the motivation for vaccination. [...]